Disclosure of the internal transport phenomena in an air-cooled proton exchange membrane fuel cell— part II: Parameter sensitivity analysis. (20th May 2021) - Hu, M.; Zhao, R.; Pan, R.; Cao, G.
Abstract: The operating and designing parameters have significant influences on the performance of an air-cooled proton exchange membrane fuel cell. Figuring out the parameter sensitivity helps select the appropriate operating point and the geometry size for a fuel cell. In this paper, parameter sensitivity analysis is conducted for the performance and the internal transport phenomena of an air-cooled proton exchange membrane fuel cell based on different air stoichiometries, air relative humidities and air flow field designs. The numerical results show that large air stoichiometry helps lower the single cell temperature, keeps the membrane better hydrated, and improves cell performance. Especially, the fluctuation of water content always exists periodically for the case of different air stoichiometry, where the minimum value of water content appears underneath the cathode channel in contrast to the maximum value appearing underneath the cathode rib. Furthermore, the maximum periodic fluctuation amplitude of water content is even more than 8 for the case of air stoichiometry of 150. The water flooding phenomenon becomes severe with the increase of air stoichiometry. Air with larger relative humidity also increases the single cell performance by improving the hydration of the membrane. However, water flooding becomes worse with the increment of air relative humidity. The narrower channel design for the cathode flow field not only leads to a more uniform current density distribution but also keeps the membrane better hydrated and thus enhances the cell performance. Highlights: A full map of the internal transport phenomena of an AC PEMFC is presented. The water content always oscillated periodically in the hydrogen flow direction. Liquid water is easier to appear at larger air stoichiometry. Single cell with narrower channel shows more uniform current and water content. Lowering the temperature is a key point in the design of an AC PEMFC.